Georreferenciação em dispositivos móveis num contexto industrial - Nuno Silva Santos (2014)
With widespread access to mobile devices, specifically smartphones, new windows open for creating innovative applications through the use of integrated technologies in hardware. Some of these technologies such as inertial sensors available, Wifi and GPS system, allow the creation of very useful tracking systems for the most diverse areas. The problem of localization is however limited by the impossibility of the use of GPS indoors. So, some methods of indoor location were studied during this thesis, including techniques based on the use of radio signals, sound waves, image analysis, infrared, inertial sensors, etc.. The implementation of the localization system will be carried out in a lead company, in this particular case Sorgal. The work discusses some solution perspectives through techniques based on time difference of arrival between transmissions of radio and ultrasonic signs, both for the location of equipment of the plant, as for the location of people, with the objective to create site maps that promote eco-efficiency. It also covers the best tools for developing mobile applications, where has been chosen to use Phonegap and JQueryMobile. Each of these solutions are grounded in the theoretical point of view and based on the results obtained by other existing implementations. This document also covers the validation of the work done. Although the application to a specific plant, the proposal seeks to provide a platform working base for applications in the industrial field.